Recent Advances in Applied Microbiology and Food Sciences - Kieliszek, Marek; Kowalczewski, Przemyslaw Lukasz (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Progressive changes in technology also cause changes in the methods used in food research, including microbiological aspects. The cooperation of research centers with industry is also important, as it poses new challenges to science. This reprint is devoted to the latest achievements in analytics, and to the application of new methods in food production technology. We present both original research and review articles focused on recent advanced technology in food science and microbiology, especially modern methods of the production and testing of food as well as the sustainable development of agriculture and the food industry. This topic will cover research on microbiological food ingredients and related topics such as microbial metabolites with application in food and feed as preservatives, texturants, and beneficial microorganisms, and methods to study and modify microbiota.